2021
DOI: 10.3390/pathogens10040468
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Insights into Newborns with Congenital Zika Infection

Abstract: Zika virus (ZIKV), an emerging virus belonging to the Flaviviridae family, causes severe neurological clinical complications and has been associated with Guillain-Barré syndrome, fetal abnormalities known collectively as congenital Zika syndrome, and microcephaly. Studies have shown that ZIKV infection can alter cellular metabolism, directly affecting neural development. Brain growth requires controlled cellular metabolism, which is essential for cell proliferation and maturation. However, little is known rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In the virological field, the first metabolomics study was reported in 2006, and analyzed over sixty metabolites during human cytomegalovirus infection (Munger et al, 2006). Since then, a variety of viruses have been demonstrated to alter multiple metabolic pathways in cells, like glycolysis and fatty acid synthesis, and have expanded the number of cellular metabolites (Birungi et al, 2010;Ritter et al, 2010;Hollenbaugh et al, 2011;Delgado et al, 2012;Sanchez et al, 2017;Tian et al, 2019;Li et al, 2021;Nunes et al, 2021;Pant et al, 2021;Wang et al, 2021). We have constructed a wild-type SVA (CH-LX-01-2016) using reverse genetics (Liu et al, 2021a), and more recently have revealed a proteomic profile of BSR-T7/5 cells inoculated with this virus at 12 hpi (Liu et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…In the virological field, the first metabolomics study was reported in 2006, and analyzed over sixty metabolites during human cytomegalovirus infection (Munger et al, 2006). Since then, a variety of viruses have been demonstrated to alter multiple metabolic pathways in cells, like glycolysis and fatty acid synthesis, and have expanded the number of cellular metabolites (Birungi et al, 2010;Ritter et al, 2010;Hollenbaugh et al, 2011;Delgado et al, 2012;Sanchez et al, 2017;Tian et al, 2019;Li et al, 2021;Nunes et al, 2021;Pant et al, 2021;Wang et al, 2021). We have constructed a wild-type SVA (CH-LX-01-2016) using reverse genetics (Liu et al, 2021a), and more recently have revealed a proteomic profile of BSR-T7/5 cells inoculated with this virus at 12 hpi (Liu et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports of serine and proline deficiencies were associated with neurodegenerative disorders and intrauterine growth retardation [41]. ZIKV studies reported amino acid metabolism downregulation in the brain of ZIKV‐infected mice embryos [42], and specifically the serine metabolism dysregulation in ZIKV‐infected newborn serum [43]. Finally, a genome‐scale metabolic stoichiometric model determined that CHIKV, DENV, and ZIKV viruses cause a negative regulation of serine metabolism [44].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a rise in phosphatidylethanolamine (PE) has been observed in Zika virus-infected patients [11] . Levels of glucose or mannose are decreased, and significant alterations have been made to the metabolic pathway associated with Nicotinamide adenine dinucleotide (NAD+) [12,13] . The metabolic pathway associated with Nicotinamide adenine dinucleotide (NAD+) is significantly altered.…”
Section: Applications Of Metabolomics To Viral Infectious Diseasesmentioning
confidence: 99%